The elasticity of electricity demand and carbon emissions reductions in the residential sector: Evidence from a tariff shift in Russia - Salim Turdaliev (Charles University in Prague, Institute of Economic Studies (IES), 2021)
In this paper, I estimate the price elasticity of residential electricity demand using household-level panel data for Russia. The study takes advantage of the variation in tariffs across regions and over time, as well as the introduction of increasing block rate (IBR) tariff schemes in a number of regions. I show that in those regions consumers appear to be aware of the block cut-offs, even though the latter are household and dwelling-specific, to the point that there are a total of 35 different tier cut-offs. Based on these results, I estimate the price elasticity of electricity demand to be around -0.09. I also predict the associated changes in electricity consumption, CO2 emissions, and revenues if similar IBR policies are implemented countrywide.
Keywords: Q41; Q48; L98; L94; 330; residential electricity demand; transition economy; natural experiment; increasing block rates; attentiveness; CO2 emissions